A master’s euphonium recital and program notes - Unger, Nichole (Kansas State University, 2016)
This master’s report focuses on the history, brief analysis, and pedagogy of the four works performed on February 15, 2016 for the author’s Master’s Recital. The first chapter explains the work Pantomime by Philip Sparke. It contains a short biography of Philip Sparke, an in-depth background on the composition of the work, and a theoretical and pedagogical look at the piece. The second chapter centers on Fantasia by Gordon Jacob. This brief biography will explore Jacob’s compositional output and legacy, and the theoretical analysis will focus on his use of chromatics and the interplay between the piano and the euphonium. The pedagogical analysis will focus on performance techniques and practice. The third chapter is devoted to Blue Lake Fantasies, an unaccompanied work for solo euphonium by David Gillingham. The biography will focus on Gillingham’s contribution to euphonium repertoire, specifically and the history of where and why this work was written. There will be a concise theoretical analysis followed by a heavily pedagogical analysis, which will break down the performance techniques used in each of the five movements. The final chapter of the report is about David Werden’s euphonium arrangement for two euphoniums and piano of Believe Me If All Those Endearing Young Charms by Simone Mantia. This chapter will present a short biography of Mantia explaining his historical significance, a brief theoretical analysis, and a pedagogical analysis that focuses on the duet aspect of this piece.
Keywords: Musical performances; Pantomime Philip Sparke; Fantasia Gordon Jacob; Blue Lake Fantasies David Gillingham; Believe Me If All Those Endearing Young Charms Simone Mantia